A History of Western Pharmacy in China - Chiu, Patrick (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book represents an important contribution to the field as it is the first to provide a detailed account of the interaction between Chinese and western medicine from a pharmacy perspective over a period of two millennia with an emphasis on the modern period from 1800-1949. None of the existing historiography on the relationship between TCM and western medicine has so far explored pharmaceutical aspects in detail. This book therefore fills an important gap in the literature and is likely to become a key resource for further study. It will be of interest to a wide audience, including pharmaceutical, imperial, and business historians, and should be essential reading for pharmacy students. But it will also be of interest to a general readership curious about the history of pharmacy in China and of western influences on Chinese medicine. Stuart Anderson, BSc, MA, PhD, FRPharmS Editor-in-Chef, Pharmaceutical Historian, Emeritus Professor of Pharmacy History, London School of Hygiene & Tropical Medicine Readers of this book, to Chiu's credit, will be exposed to the nuanced cultural, medico-scientific, and business interactions that shaped Western pharmacy in China. Chiu puts a spotlight on the various materials, techniques, and processes of drug formulation and mass manufacture - and he rightly illustrates how pharmacy was substantiated as big business and mass manufacture. In analyses that incorporate materia medica and so-called dangerous drugs, such as opium, Chiu also articulates the complicated entangled histories of the movement, circulation, and translation of both pharmacy knowledge and goods. Yet, he appropriately acknowledges and evaluates non-Western epistemologies and practices that intermingled with Western ideas to create a novel type of pharmacy and pharmaceutical industry in China. Lucas Richert, PhD Professor & George Urdang Chair in Pharmacy History, UW-Madison Executive Director, American Institute of the History of Pharmacy Patrick Chiu's book, A History of Western Pharmacy in China, effectively presents an unbiased perspective when discussing the contributions of expatriate pharmacy academics towards the development of China's pharmaceutical profession and the modern drug industry in the first half of the twentieth century. Chiu's impartial approach and well-researched content make it a recommended resource for understanding the historical development of pharmacy in China. Kazushige Morimoto Ph.D. D.Min, Education System - Qualified Pharmacist, President, The Japanese Society for the History of Pharmacy .
The Beginnings of Western Influence on Chinese Medicine, 200 BCE - 1800 CE -- Trade Wars and the Emergence of Western Pharmacy -- Union Medical College and the "Cradle of Modern Medicine" -- The Rise of Western Chemists -- "Opium Cures", Proprietary Medicine and Soda Water -- Pharmaceutical Education and Manpower Development.
Keywords: Medicine -- History; China -- History; Pharmacy; Pharmaceutical chemistry; Imperialism; History of Medicine; History of China; Pharmacy; Pharmaceutics; Imperialism and Colonialism